Effect of physical parameters on ᴅ-xylonic acid production using recombinant E. coli BL21 (DE3) - Nurul Atikah, Mohd Rodzri; Salwani, Md Zain; Rafidah, Mohamed Ali Hanapiah; Rozaimi, Abu Samah; R. M., Illias (Elsevier Ltd, 2019)
ᴅ-xylonic acid is a five-carbon organic acid that has gain increasing interest due to its broadly flexible application in fields such as foods, pharmaceutical and agriculture. Microbial production of ᴅ-xylonic acid can be done by using many species of Pseudomonas, Acetobacter, Gluconobacter and the latest finding was by engineered microorganism. In this study, recombinant E. coli BL21 (DE3) is used to produce ᴅ-xylonic acid from ᴅ-xylose and the effect of temperature, initial pH of medium and agitation rate on ᴅ-xylonic acid production is determined. Fermentation was carried out using super optimal broth medium in shake flasks for 24 hours. Results indicate that ᴅ-xylonic acid concentration was as high as 9.95 g L-1 with yield of 0.91 g/g ᴅ-xylose from 10 g/L when governed under temperature of 37°C, initial pH of medium pH 7 and agitation rate 200 rpm.